Predictive performance of qSOFA in confirmed COVID-19 patients presenting to the emergency department - Farhad Heydari; Saeed Abbasi; Kiana Shirani; Majid Zamani; Babak Masoumi; Saeed Majidinejad; Mahsa Sadeghi-Aliabadi; Mohammadreza Arbab (Tzu Chi Medical Journal)
Objectives: It is critical to quickly and easily identify coronavirus disease 2019 (COVID-19) patients who become severely or even critically ill. Thus, this study was conducted to determine the accuracy of the quick Sequential Organ Failure Assessment (qSOFA) score in predicting the severity and mortality of COVID-19 patients. Materials and Methods: This was a prospective observational study of COVID-19 patients admitted to the emergency department (ED) between June 22, 2021, and November 21, 2021. The clinical characteristics of the participants were collected by the emergency physicians. The correlation of the qSOFA, Systemic Inflammatory Response Syndrome criteria (SIRS), Pneumonia Severity Index (PSI), and confusion, urea, respiratory rate, blood pressure, 65 years of age and older (CURB-65) scores for 14-day mortality were evaluated. The area under a receiver operating characteristic (AUROC) curve analysis was calculated to compare the effectiveness of qSOFA, SIRS, PSI, and CURB-65 to predict severe disease. Results: Eight hundred and ninety-four subjects were included. Of them, 721 patients (80.6%) survived after 14 days of admission. The mean age was 58.92 ± 17.80 years, and 551 subjects (61.6%) were male. Nonsurvived patients were significantly older (51.09 ± 23.60 vs. 38.10 ± 18.24, P = 0.004) and had more comorbidities (diabetes mellitus, respiratory, cardiovascular, and cerebrovascular disease) in comparison with survived patients. For COVID-19 mortality prediction, the AUROCs of qSOFA, CURB-65, PSI, and SIRS score were 0.799 (95% confidence interval [CI 0.771–0.825]), 0.829 (95% CI [0.803–0.853]), 0.830 (95% CI [0.804–0.854]), and 0.759 (95% CI [0.730–0.787]), respectively. All scores were good predictors of COVID-19 mortality. Conclusion: The qSOFA was more successful than SIRS in predicting mortality for COVID-19 patients and was similar to CURB-65 and PSI. Therefore, the qSOFA score can be considered a simple and rapid screening tool for identifying high-risk patients.